NGcGM3 Ganglioside: A Privileged Target for Cancer Vaccines - Luis E. Fernandez; Mariano R. Gabri; Marcelo D. Guthmann; Roberto E. Gomez; Silvia Gold; Leonardo Fainboim; Daniel E. Gomez; Daniel F. Alonso (Clinical and Developmental Immunology)
Active specific immunotherapy is a promising field in cancer research. N-glycolyl (NGc) gangliosides, and particularly NGcGM3, have received attention as a privileged target for cancer therapy. Many clinical trials have been performed with the anti-NGc-containing gangliosides anti-idiotype monoclonal antibody racotumomab (formerly known as 1E10) and the conjugated NGcGM3/VSSP vaccine for immunotherapy of melanoma, breast, and lung cancer. The present paper examines the role of NGc-gangliosides in tumor biology as well as the available preclinical and clinical data on these vaccine products. A brief discussion on the relevance of prioritization of cancer antigens in vaccine development is also included.